Semantic Dynamics Between Text And Context Selected Models From The Grand Lexicon Of Precious Gems/ دينامية المعنى بين النص والسياق نماذج مختارة من معجم النفائس الكبير - Omar Hazem Azez Al-Heety; Qusay Jaddoa Ridha Al-Heety (Ijaz Arabi Journal of Arabic Learning, 2026)
This research seeks to investigate the phenomenon of semantic dynamics by studying the dialectical relationship that connects a text with its various contexts. This research is based on a practical application that draws its models from "The Grand Lexicon of Precious Gems" by the author Kazem Al-Abboud, which is considered a prominent example in employing the contextual approach to present meanings. In his analysis, the researcher relies on extrapolating a wide range of heritage texts, encompassing both poetry and prose. He presents the word through its live contextual examples, illustrating how word meanings are formed and how they are colored by the diversity of the surrounding textual and cultural environments. This research is based on a descriptive-analytical approach, with a focus on the contextual method as the primary tool of analysis. The research methodology is based on the deliberate selection of a sample of the lexicon's entries, studying them with a degree of depth and precision. In concluding the analysis, the study emphasizes the pivotal importance of the contextual method in the fields of modern linguistic and semantic studies, while highlighting the practical value of "The Grand Lexicon of Precious Gems" as a link between the rich heritage of Arabic lexicography and modern methods of text and discourse analysis.